Credit valuation adjustment modelling during a global low interest rate environment - Petr Macek; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2015)
The 2008/2009 global crisis highlighted the vulnerabilities and inter-dependencies in the financial system including the global over-the-counter (OTC) derivatives markets, where significant counterparty credit risk prevails. In this paper, we deal with risk under Basel III banking regulation and provide credit valuation adjustment (CVA) modelling, which is a measure of the market value of counterparty credit risk. We use simulated data to develop a stress test model to determine the impact of counterparty credit risk on bank capital regulatory requirements. We developed six scenarios of different interest rate levels and from these scenarios we computed the exposure levels and CVA. Consequently, based on CVA modelling, we estimate the impact of an interest rate hike on portfolios of the top 3 Czech banks (éCeská spoéritelna, éCSOB and Komerécní banka) and top 3 US banks (Bank of America, Citibank and JP Morgan). We conclude that i) the analyzed Czech banks report sufficient capital buffers to withstand increase of interest rates in any scenario; ii) the observed US banks with high exposure to derivatives would face significant capital shortfalls if the interest rates increase rapidly.
Keywords: G21; G28; G32; G33; 330; bank capital; Basel III; counterparty credit risk; credit valuation adjustment; market risk